PENGARUH KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP MOTIVASI KERJA SERTA IMPLIKASINYA PADA KOMITMEN PEGAWAI DI KANTOR-KANTOR KEMENTRIAN AGAMA SE PROPINSI BANTEN - Mr Mukrodi; Mr Wahyudi (Jurnal Ekonomi Efektif, 2018)
Civil Servants (PNS) are state servants whose duties and obligations are to serve the community, so that their work behavior is professional, responsible and provides excellent service. The purpose of this study was to find, describe, and analyze the influence of leadership and organizational culture on work motivation and its implications for the commitment of employees in the Ministry of Religion Offices in Banten Province. This study uses a quantitative method with a total of 170 respondents, and the analysis method used is Structural Equation Models (SEM). The results of the study on structure I show that together leadership and organizational culture has significant effect on work motivation, but partially the leadership have negative and insignificant influence, while organizational culture have a significant effect on work motivation. Furthermore, the results of the study on structure II show that together leadership, organizational culture and work motivation has significant effect on commitment, but partially the three variables have no significant effect